Contemporary Implications of Ibn Sina's Epistemology for Islamic Political Leadership in the Indonesian Context - Ushansyah; Normuslim; Muhammad Taufiq; Olis (Profetika: Jurnal Studi Islam, 2026)
Objective: This article aims to examine Ibn Sina's epistemological and metaphysical foundations in constructing the concept of political authority within the Islamic intellectual tradition, with particular emphasis on al-Raʾīs al-Awwal as the ideal model of prophetic leadership. Theoretical framework: The study is grounded in Ibn Sina's theory of knowledge, metaphysics, and political philosophy, emphasizing the interaction between reason, revelation, and ethical governance. Literature review: Previous studies have predominantly discussed Ibn Sina's epistemology from philosophical and theological perspectives, whereas limited attention has been given to its political implications and its application to modern Islamic leadership, particularly within Indonesia's democratic and pluralistic society. Method: This study employs qualitative library research using a hermeneutical and interpretive analytical approach. Classical and contemporary sources are critically examined to reconstruct Ibn Sina's political epistemology and evaluate its contemporary significance. Results: The study demonstrates that genuine knowledge is attained through the illumination of the human intellect by the Active Intellect. Prophets possess the highest degree of intellectual and spiritual perfection, enabling them to receive comprehensive knowledge and establish legitimate authority. This epistemological foundation generates a rational-prophetic leadership model characterized by intellectual excellence, ethical integrity, independent reasoning, justice, public accountability, and unwavering commitment to people-centered governance. Such leadership provides a philosophical response to challenges including identity politics, abuse of power, declining political ethics, and digital populism. Implications: These findings offer a normative framework for strengthening ethical political leadership, governance, and public trust within contemporary Indonesian Islamic politics. Novelty: This article reconstructs Ibn Sina's epistemological and metaphysical thought into a contemporary rational-prophetic leadership model centered on al-Raʾīs al-Awwal, integrating philosophical principles with practical political ethics and authentic personal leadership for democratic governance.